Advanced photo-annealing of indium zinc oxide films for thin-film transistors using pulse UV light - Park, Sang Cheol; Kim, Dongwook; Shin, Hyunji; Lee, Do Kyoung; Zhang, Xue; Park, Jaehoon; Choi, Jong Sun (Journal of Information Display, 2016)
An ultra-fast and simple method for forming high-performance metal oxide semiconductor by a solution process based on sol-gel condensation in ambient air using pulse ultraviolet-light annealing is proposed for the thin-film transistor (TFT) application. Even a small amount of light absorbance by the transparent metal oxide film provide sufficient energy to carry out sol-gel condensation because of the extremely high peak energy and broad irradiation spectrum of the xenon lamp used in this study. The fabricated indium zinc oxide TFTs had a field-effect mobility of 2.4 cm 2 V −1 s −1 , which is comparable to a device performance of 2.7 cm 2 V −1 s −1 obtained through thermal annealing.